An assessment of knowledge and practices relating to the usage of sanitary pads - Rai, Namrita; Crimbly, Faine; Aftab, Summaya; Baig, Aleena; Fernandes, Nathaline; Mahmood, Syed Uzair (International Journal Of Community Medicine And Public Health, 2019)
Background: The knowledge of the proper use, disposal of sanitary pads, and its related side effects during menstruation is a vital aspect of a woman’s well-being. Use of sanitary pads appropriately and replacing them on time are essential practices needed to maintain menstrual hygiene. Failure to do so may lead to detrimental consequences that could affect the health of women and make them susceptible to reproductive tract infections. Objectives were to assess a range of factors considered by female about the usage of sanitary pads and the various methods employed regarding its disposal. Methods: A cross sectional study was conducted from March to June 2018, in the city of Karachi, by students of Jinnah Sindh Medical University. A sampling technique was used to select 391 females. Data collection was carried out using a structured questionnaire, by convenience sampling. Response of the participants was acquired using a 5-point Likert scale. Results: In total, 391 females from the city took part in this study; their ages ranging between 15-45 years. 95.7% of these females preferred sanitary pads over cloth, tampons, menstrual cups and toilet paper. Many women using sanitary pads believed, pads should be replaced often while menstruating and failure to do so may increase the risk of contracting infections (p≤0.01). Conclusions: The findings showed that a significant number of women are aware of the risks associated with sanitary napkins and have adequate knowledge related to its proper usage. The study also presented no significant risk of adverse effects associated with the use of sanitary pads.